Sustainable intensification of wheat production under smallholder farming systems in Burera, Musanze and Nyamagabe districts of Rwanda. (22nd June 2022) - Cyamweshi, Athanase Rusanganwa; Nabahungu, Nsharwasi Léon; Mirali, Jackson Cirhuza; Kihara, Job; Oduor, George; Rware, Harrison; Sileshi, Gudeta Weldesemayat
Abstract: The productivity of wheat is low on smallholder farms in Rwanda. Although mineral fertiliser use is being promoted as a sustainable intensification (SI) pathway, little is known about the nutrient use efficiency and profitability of various fertiliser inputs in Burera, Musanze and Nyamagabe districts of Rwanda. The objective of this study was to assess the use of combinations of nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg), zinc (Zn) and boron (B) in wheat production in terms of nutrients management specifically, crop yield, production risk, input use efficiency and economic returns on smallholder farms. The study was conducted in three wheat-growing regions of Rwanda (i.e., Nyamagabe, Musanze and Burera districts) with contrasting soil conditions. The treatments included combinations of different levels of N (0, 30, 60, 90 and 120 kg ha −1 ) with P (0, 7.5, 15 and 22.5 kg ha −1 ) and K (10, 20 and 30 kg ha −1 ) and the control with no applied nutrients. A diagnostic treatment composed of 90 kg N, 15 kg P, 20 kg K, 10 kg Mg, 2.5 kg Zn and 0.5 kg B ha −1 was also included. Mean grain yield and its variability, rainfall use efficiency (RUE), agronomic use efficiency (AE) of N and P and the value cost ratios (VCRs) were calculated to assess the sustainability of the nutrient rates. Across all sites, wheat grain yield and RUE increased with increase in N rates up to 90 kg N ha −1, beyond which no further increase was observed. The highest wheat yield (5.5 t ha −1 ) and RUE (6.6 kg ha −1 mm −1 ) with the lowest production risk (coefficient of variation [CV] = 20%) were recorded in the diagnostic treatment. Although the highest AEN and AEP were recorded at lower N and P levels, the CVs of VCR were high (>64%), indicating higher production risk to wheat farmers. In all cases, an optimum VCR (5.6), with the lowest CV (44.4%), was recorded in the diagnostic treatment. We conclude that application of 90 kg N, 15 kg P, 20 kg K, 10 kg Mg, 2.5 kg Zn and 0.1 kg B can guarantee a more SI of wheat production in Burera, Musanze and Nyamagabe districts of Rwanda.